Cost-effectiveness analysis (CEA) of IMRT plus C12 boost vs IMRT only in adenoid cystic carcinoma (ACC) of the head and neck - Jensen, Alexandra; Debus, Jürgen (Radiation oncology, 2019)
Particle therapy provides steep dose gradients to facilitate dose escalation in challenging anatomical sites which has been shown not only to improve local control but also overall survival in patients with ACC. Cost-effectiveness of intensity-modulated radiotherapy (IMRT) plus carbon ion (C12) boost vs IMRT alone was performed in order to objectivise and substantiate more widespread use of this technology in ACC.
Gesehen am 01.04.2020